Representasi Keterwakilan Penyandang Disabilitas dalam Dewan Perwakilan Rakyat - Muslim, Reyhandhi Alfian; Purimaharani, Andina Elok (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
Democracy guarantees basic human rights, such as the right to life, the right to form political parties, and the right to be elected and to vote in general elections, because with democracy, the basic rights of every human being are guaranteed, creating equality for all citizens without any differences, especially people with disabilities. The purpose of this paper is to analyze the fulfillment of representation of persons with disabilities in the House of Representatives and to find out the ideal construction in building political representation for persons with disabilities. This type of legal research is normative legal research or doctrinal research, which is research based on reading legal materials and primary and secondary legal studies. This research reveals that there are obstacles and constraints for persons with disabilities to be able to have representation in the DPR, these obstacles are in the form of obstacles to the electoral system, parties, campaign systems, and election financing for persons with disabilities. Accessibility of political rights for persons with disabilities still cannot be fulfilled properly. As well as revealing that there is a need for ideal legal construction in building representation of persons with disabilities. Legal construction can be in the form of an affirmation policy for persons with disabilities. Because the state provides equal opportunities in government. With this legal construction, it is hoped that the political representation of persons with disabilities in the DPR will be achieved.